The Effect of Using Debate Strategy On 11th Grade Students Speaking Skill in SMA (SLUA) Saraswati 1 Denpasar - I Made Agus Sastra Wiguna; Igna Wijaya Mahardika; I Dewa Gede Rat Dwiyana Putra (KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to find out the effect Debate strategy and Discussion Strategy on the speaking skills of Eleventh grade students at SMA (SLUA) Saraswati 1 Denpasar. The researcher used a quantitative method with a Quasi-experimental design. The sample consist of 30 students for the experimental group and 30 students for comparison group. XI 3 Regular as the experimental group and XI 4 regular as the comparison group. The research instrument used is speaking test. In this study, the researcher collected the data from the pre-test and post-test. Data analysis using descriptive statistical analysis, test normality, test homogeneity and A Mann Whitney U test. Based on the calculation using SPSS application, The result showed p = >.001. Based on the result, there was no significant effect between the two group. Based on this finding, it can be concluded that Debate strategy and Discussion strategy give no significant effect for improving students speaking skill.